A Socio Behavioural Perspective for Understanding and Managing Behaviour Problems in Children with Epilepsy - C. A. Cull; S. W. Brown (Behavioural Neurology)
In this paper, reasons for the occurrence of interictal behaviour disturbance in children with epilepsy, and the management of such problems, are considered. The search for a direct relationship between epilepsy related variables and behaviour disorders is far from conclusive. While such a relationship may exist with respect to ictal behaviour problems, this line of investigation is of limited value in respect of its implications for the management of interictal problems. In the latter case it is proposed that organic factors may be considered to be a risk factor. In addition, the negative psychosocial sequelae of a diagnosis of epilepsy can result in conditions which are likely to foster the development of inappropriate behaviours. Learning theory would further suggest that environmental contingencies have a role to play in the shaping and maintenance of such behaviours. This broader framework for conceptualising the development and maintenance of interictal behaviour disorders has clear management implications. Clinical examples of the successful application of this approach to the management of persistent behavioural problems in two young people with epilepsy are presented.